Validation of internal control genes for quantitative real-time PCR under different experiment conditions in Multiple Myeloma - Hossain, Md Sabbir (Journal of BioScience and Biotechnology, 2019)
Multiple myeloma (MM) is a cancer of malignant plasma cells in the bone marrow which might lead to the development of one or more clinical manifestations such as bone destruction, anemia, renal insufficiency etc. Gene expression analysis using quantitative real-time PCR (qRT-PCR) is imperative to understand the development mechanisms of MM. Housekeeping genes (HKGs) are commonly used as endogenous controls to normalize quantitative real-time PCR (qRT-PCR) data for gene expression analysis. However, recent studies argue that the expression of HKG genes may vary under certain experimental condition. In addition, no studies have been found on the expression analysis of HKGs by qRT-PCR in MM. Therefore, the present study was designed to validate reference genes for qRT-PCR normalization through observing the effects of hypoxia, serum stimulation and Myc inhibition on the expression of five HKGs (18S, ACTB, B2M, GAPDH and TBP) in three different myeloma cell lines (ANBL-6, IH-1 and INA-6). Four different approaches (Best Keeper, ∆Ct approach, GeNorm, and NormFinder) followed by comprehensive methods were used for the evaluation and selection of reference gene. Most stable expression of 18S in hypoxic and serum stimulation experiment while constant expression of B2M in Myc inhibition made them an excellent combination to normalize qRT-PCR data in gene expression analysis in MM.